Insights into the Substrate Uptake Mechanism of Mycobacterium Tuberculosis Ribose 5-Phosphate Isomerase and Perspectives on Drug Development - Bartkevihi, Leonardo; Caruso, Ícaro P. [UNESP]; Martins, Bruna; Pires, José R. M.; Oliveira, Danielle M. P.; Anobom, Cristiane Dinis; Almeida, Fabio C. L. (MDPI, 2023)
The active site of the dimeric ribose 5-phosphate isomerase B (RpiB) contains a solvent-exposed barrier formed by residues H12, R113, R137, and R141, which is closed upon the complexation of phosphate. The substrate ribose 5-phosphate (R5P) has to overcome the surface barrier to reach an internal cavity and then bind in the linear configuration of ribose to the interface between the two subunits. NMR and molecular dynamics simulation are suitable methods to describe the transient nature of the RpiB active site and help our understanding of the mechanism of substrate entrance. In this study, we show that the entrance of the nucleotides AMP/ADP into the internal cavity of mycobacterium tuberculosis RpiB (MtRpiB) does not involve a canonical open/close-lid conformational transition usually observed in many enzymes. Instead, a flipping mechanism in which the nucleotide phosphate interacts with the surface barrier followed by the flip of the nitrogenous base and ribose is responsible for changing the substrate/ligand orientation from a solvent-exposed to a buried state. Based on these results, we propose a substrate/inhibitor uptake mechanism that could provide a basis for rational drug design using MtRpiB, which is an essential enzyme and a good target for drug development.
Keywords: adenosine monophosphate; molecular dynamics simulations; nuclear magnetic resonance (NMR); ribose 5-phosphate isomerase; substrate uptake